The current state of electrospinning technology and its prospects for the future - Yeskermessov, D.; Tabiyeva, Y.; Aringozhina, Z.; Booth, M.; Tussupbekova, A.; Pazylbek, S. (Karagandy University of the name of acad. E.A. Buketov, 2023)
With the development of nanotechnology and modern research methods, the use of biodegradable polymer materials in various sectors of human life is of interest not only to the scientific world community, but also is a way to solve one of the global problems related to resource conservation and environmental protection. Polyvinyl alcohol-based materials have been widely used in various fields due to their biological and physical properties, such as biocompatibility, biodegradability, antimicrobial ability, non-toxicity and the ability to easily form a film. One of the methods of obtaining polymer films that exist today is electrospinning, the advantages of which are the relative simplicity of the technological process and the possibility of obtaining continuous nanofibers from both synthetic and natural polymers. In this work, the influence of various process parameters on the formation of nanofiber mats from a biodegradable synthetic polymer by electrospinning was studied. The technology of wet spinning, melt spinning and dry spinning is discussed. A number of experimental studies have been carried out to identify optimal modes of obtaining nanofibers from polyvinyl alcohol with the most homogeneous structure without the formation of defects.
Электрспиннинг технологиясының қазіргі жағдайы және оның болашағы
Современное состояние технологии электроспиннинга и ее перспективы
Keywords: electrospinning; technological parameters; nanofibers; polyvinyl alcohol (PVOH); nonwoven mats; SEM; nanofiber diameter; biodegradable polymer material